Social media usage in family communication about genetic information: 'I no longer speak with my sister but she needed to know'. Issue 1 (9th July 2020) - Leighton, Sarah; Forrest, Laura E.; Young, Mary‐Anne; Delatycki, Martin B.; Lynch, Elly
Abstract: The use of social media has become a ubiquitous form of communication. Little is known about whether social media is used in families to assist with the communication of genetic information. This study aimed to understand if and why individuals use social media to communicate genetic information to at‐risk relatives. Individuals with either a pathogenic variant in a cancer‐predisposing gene or a heterozygous pathogenic variant in an autosomal or X‐linked recessive gene were surveyed about communicating genetic information to their at‐risk relatives and their use of social media to assist this process. Surveys were sent to 323 individuals from a reproductive carrier screening program and 250 individuals from a familial cancer center. The 128 responses (response rate 25.2%) showed that while most participants (79.0%) did not use social media to communicate genetic information, those that did use social media (21.0%) found it to be helpful as it was easy, accessible and allowed individuals to overcome communication barriers. Genetic professionals should be aware that social media is being used by individuals to assist family communication about genetic information and should discuss this method of communication with individuals who are faced with communicating genetic information with their family.